Association of shift work with depression and anxiety in middle-aged adults: a large cross-sectional study among Iranian industrial manufacturing employees. Issue 4 (10th August 2020) - Alizadeh, Zeinab; Roohafza, Hamidreza; Feizi, Awat; Sarrafzadegan, Nizal
Abstract : Purpose: This study aimed to examine the association of shift work with depression and anxiety in a large sample of formal and contractual employees of a mill steel company, Isfahan, Iran. Design/methodology/approach: This cross-sectional study was performed in 2014 among 3, 060 formal and contractual employees of a mill steel company Isfahan, Iran, randomly selected from 16, 000 people. Data gathering was done by some validated Iranian version of self-administered questionnaires including, International Physical Activity – Short Form, Effort–Reward Imbalance, Hospital Anxiety and Depression Scale. Logistic regression was used as the main statistical method. Findings: The results showed individuals in the rotating shift compared with day shift had a higher risk of depression (OR: 1.43; 95% CI: 1.12–1.84). Whereas after adjustment for various confounders, this relationship was not significant (OR: 1.19; 95% CI: 0.81–1.76). Anxiety was not associated with shift work, both in crude and adjusted models (OR: 1.08; 95% CI: 0.81–1.44) and (OR: 0.90; 95% CI: 0.67–1.19), respectively. Research limitations/implications: Owing to the cross-sectional design of this study, cause–effect relationships could not be inferred from our findings. All the data used in the present analysis were collected by self-administered questionnaires. Practical implications: Although our findings did not show significant association between shift work and mental health, further studies are suggested for obtaining informative data worldwide in this regard among workforce particularly among industrial employees. Originality/value: Few studies have addressed the effects of shift work on mental health among industrial employees worldwide, and there is no study in developing countries.